Board Diversity and Firm Performance: Evidence from Indonesia - Rita Rahayu; Halimah Tusya Diah (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to examine the impact of board diversity of company’s board of commissioner and board of director on the financial performance. This study was motivated by two factors. Firstly, there is limited number of studies associated to board diversity existence on company performance, especially in Indonesia. Secondly, the diverse board is not mandatory for companies in Indonesia as developing country, which means there is no obligation for companies to make a diverse boardroom. In this study, the board of diversity consist of board gender, board nationality and board age, while the firm performance is proxied by Return on Asset, Return on Equity and Tobin’s Q. This study used purposive sampling and the samples comprise all manufacturing and banking companies listed on Indonesia Stock Exchange during 2016-2017. By using independent t-test, this study found only the existence of foreign board members for both Board of commissioner and Board of Director which has impact on company performance. Meanwhile, the board gender and board age have inconsistent result on company financial performance. This study provides new insight for regulator and practitioner on the need of diverse board as a way to improve performance and enable them to manage the complexity within the company